Pemberdayaan Kreatifitas Ibu-Ibu Pemberdayaan Kesejahteran Keluarga (PKK) Melalui Pelatihan Pembuatan Bucket dan Pemasarannya di Desa Karang Patihan Pulung - M Akrom Tariqul Huda; Ibnu Muchlis (Social Science Academic, 2025)
The purpose of this training is to develop the creativity of mothers to empower family welfare. There are many efforts that can be made, one of which is to provide bucket-making training to mothers so they are skilled at being creative. By holding training on making flower buckets and snacks with the aim of empowering women aged 20-35 years, this can be used as a way to increase the creativity of mothers and as a lesson about entrepreneurship. These flower and snack buckets can be economical and useful at the touch of a hand. This bucket-making training activity began with outreach to mothers about bucket-making tools and materials. Then, the next activity was to practice making flower buckets and snacks with the mothers. After it was finished, the last activity was socialization regarding the marketing of the flower buckets and snacks. This activity was carried out at the Karang Patihan Pulung village hall involving PKK women as training participants. Through this training activity, it is hoped that mothers in family welfare empowerment can shape their character and creativity. The research method used by researchers is to use the ABCD approach, which is an approach to community service. This approach focuses on an inventory of assets in the community which are assumed to be very supportive of community empowerment activities. The emphasis on reinventing assets is a hallmark of this approach. Research conducted using a method called ABCD (Asset Based Community Development) is intended to be able to explore its potential to create local-based excellence known as Appreciative Inguiry. So that business owners know their potential to develop their business with the support of INSURI students who are implementing KPM. The end result of this activity is that mothers are proficient and can be creative by themselves, develop their talents and skills in making snack buckets so that they can become high selling points and create new innovations so that consumers don't feel bored with the same bucket.